Effect of interleukin 6 blockers on body composition, adipocytokines and insulin-like growth factor 1 in patients with rheumatoid arthritis - L. V. Kondratyeva; Yu. N. Gorbunova; T. V. Popkova; A. A. Abramkin; T. A. Lisitsyna; N. V. Demin; M. E. Diatroptov; A. S. Avdeeva (Научно-практическая ревматология)
The aim – to study the effect of interleukin (IL) 6 blockers on body composition, as well as leptin, adiponectin, and insulin-like growth factor (IGF) 1 levels in patients with rheumatoid arthritis (RA) during a prospective follow-up of 6 months.Material and methods. The study included 29 patients with RA with moderate to high disease activity who were first initiated on therapy with tocilizumab 8 mg/kg/infusion intravenously (n=13) or olokizumab 64 mg subcutaneously (n=16) every 4 weeks. At two points, at baseline (T0) and at the end of observation (T1), body composition (fat mass and lean mass) was assessed using dual-energy X-ray, and leptin, adiponectin, and IGF-1 levels were determined using an enzyme immunoassay.Results. After 6 months of therapy, remission and low disease activity were achieved in 11 (84.6%) patients in the tocilizumab group and 14 (87.5%) in the olokizumab group (p=0.75). Repeated DXA was performed after 5.5 [5.5; 8.0] months; overall, BMI, fat and lean mass, leptin, adiponectin and IGF-1 concentrations increased in RA patients (p<0.05). Correlations were found between ∆ fat mass and ∆ CRP (r=–0.6; p=0.0005), ∆ leptin and ∆ fat mass (r=0.69; p=0.000048), ∆IGF-1 and ∆ lean mass (r=0.39; p=0.042). When using tocilizumab, ∆ fat mass was –0.04 [–1.1; 0.4] kg, when using olokizumab – +3.9 [2.1; 5.0] kg (p=0.00008), ∆ leptin – 0.16 [–3.84; 3.12] and 6.26 [1.94; 20.7] ng/ml, respectively (p=0.037), ∆ lean mass, ∆ adiponectin and ∆IGF-1 were comparable in the two groups (p>0.05).Conclusions. The use of both IL-6 blockers resulted in a significant decrease in disease activity after 6 months of therapy in most patients with RA, which was accompanied by an increase in BMI, fat and lean mass, as well as serum leptin, adiponectin and IGF-1 levels. The accumulation of fat mass was directly related to a decrease in the severity of inflammation, and an increase in the concentration of leptin and IGF-1 – with body composition changes. Tocilizumab, unlike olokizumab, did not significantly affect fat mass accumulation and leptin levels elevation.